Descrição e análise de contingências presentes em legislações referentes à mobilidade urbana - Lourencetti, Luiz Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The press often publishes urban mobility problems due to unplanned growth of many Brazilian cities. These informations are corroborated by government agencies such as IBGE and DENATRAN, which indicate gradual increase of the proportion of automotive vehicles per residence and the total of automative vehicles across the country. This dense and disordered urban growth can be followed by harmful consequences for the population, such as traffic jam, noise and air pollution, increase in the number of traffic accidents, unefficient public transport, among others. Considering this situation planning and proposing actions and policies related to urban mobility, avoiding or minimizing any losses or negative consequences for the population should be priorized. Planning of public policies often involves a design of cultural practices, which is intrinsically linked to the way that people interact between each other and with the environment. In this way, the set of laws available in Brazil, especially the Cities Statute and Director Plans if effectively implemented, are characterized as basic tools, providing guidance to reach a sustainable urban mobility. In this context, this study aimed to promote a functional analysis by identifying behavioral prescriptions through the description of three terms contingencies, which are directly or indirectly referenced in urban mobility laws, specifically the City Statute, the National Policy of Urban Mobility and the Participative Director Plan of the city of Bauru-SP. A descriptive method which consisted of reading the laws, identifying the terms of contingency: Antecendent Context-environmental situations which the context, condition or circumstance in which the behavior occurs or should occur; Reponse - describes and/or indicates, explicitly or implicity, the action or expected action; Consequence - directly or indirectly related to a response consequences. As results 107 complete contigencies were described...

A imprensa noticia com frequencia problemas de mobilidade urbana devido ao crescimento não planejado de muitos municípios brasileiros. Tais informações são corroboradas por agências governamentais como o IBGE e o DANATRAN, que indicam gradativo aumento na proporção de veículos automotores por domicílio e o número total de veículos automotores emplacados em todo o país, respectivamente. Esse crescimento urbano denso e desordenado pode vir acompanhado de consequências nocivas à população, como congestionamentos, poluição sonora e do ar, aumento do número de acidentes de trânsito público deficitário, dentre outros. Diante desse quadro, tornam-se imprescindíveis o planejamento e a proposição de ações e políticas públicas tematizadas pela mobilidade urbanam como forma de evitar ou minimizar eventuais prejuízos e consequências negativas à população. O planejamento de políticas públicas muitas vezes envolve um delineamento de práticas culturais, o que está intrinsecamente relacionado à maneira com que os indivíduos interagem entre si e com as demais instâncias do ambiente em que estão iseridos. Nesse sentido, o conjunto de leis disponíveis no Brasil, em especial o Estatuto da Cidade os Planos Diretores, se efetivamente concretizados, caracterizam-se como instrumentos básicos e norteadores, fornecendo diretrizes para que a mobilidade urbana ocorra de forma sustentável. Nesse cenário, o presente estudo objetivou promover uma análise funcional, identificando prescrições comportamentais, por meio da descrição de contingências comportamentais de três termos, que são direta ou indiretamente referenciadas em legislações acerca da mobilidade urbana, especificamente do Estatuto da Cidade, da Política Nacional Nacional de Mobilidade Urbana e do Plano Diretor Participativo do Município de Bauru-SP. Para isso, adotou-se metodologia descritiva que consistiu na leitura das leis, identificando os termos da...
Description and analysis of contingencies in laws related to urban mobility
Keywords: Avaliação de comportamento; Cultura; Legislação urbana; Mobilidade social; Planejamento urbano; Behavioral assessment